Degrees of success : the transitions from vocational to higher education - Hayward, Geoff; Katartzi, Evgenia; Ertl, Hubert; Hoelscher, Michael (Great debates in higher education., 2021)
Learners with a VET background experience much higher rates of attrition compared to learners entering HE with academic qualifications. Degrees of Success explores the transition from vocational to higher education, and outlines what more can be done to support and provide improved access to HE for these learners.